Different types of acupuncture and moxibustion therapy for neurogenic bladder after spinal cord injury: A systematic review and network meta-analysis study protocol - Lei, Hanzhou (Medicine (Baltimore), 2020)
BACKGROUND: The invasive surgical intervention for neurogenic bladder dysfunction (NBD) following spinal cord injury (SCI) involves permanently altering one's body system and carries many surgical related risks and medication side effects are often seen in long term usage of pharmaceutical medications. Therefore, acupuncture and moxibustion therapies have been recommended due to their efficacy, simplicity of operation, cost effectiveness and safety. This protocol is designed for systematic review and network meta-analysis, which will perform comparisons or rankings of efficacy among the currently available acupuncture and moxibustion techniques and provide evidence to guide the best practice in acupuncture and moxibustion treatments of NBD due to SCI. METHODS/DESIGN: The Cochrane Library, EMBASE, PubMed, Web of Science, CENTRAL, CNKI, The VIP Database, The Wanfang database, CDFD, CMFD will be searched from inception to November 1, 2019. All randomized controlled trials containing eligible interventions(s) and outcome(s) will be included. The quality of included trials will be assessed using the “Risk of bias” tool from the Cochrane Handbook (V.5.1.0). Data analysis will be conducted by using STATA software (Version 13.0). Continuous outcome will be indicated as mean difference (MD) or standard mean difference (SMD), and enumeration data will be presented with odds risk (OR) or relative risk (RR). RESULTS: This systematic review and network meta-analysis study aims to determine the most effective and safe approach in relieving urinary symptoms, and whether it produces better results in urodynamic examination. And a high-quality ranking of the therapeutic classes will be presented. The report will follow the PRISMA checklist for network meta-analysis. Results of the search strategy and the study selection will be presented in a PRISMA compliant flow chart. CONCLUSION: This study aims to propose a standard clinical decision-making guideline for acupuncture and moxibustion treatment of NBD after SCI.